Do Incentives Crowd Out Motivation? A Feasibility Study of a Community Vector-Control Campaign in Peru. Issue 1 (2nd January 2023) - Buttenheim, Alison M.; Castillo-Neyra, Ricardo; Arevalo-Nieto, Claudia; Shinnick, Julianna E.; Sheen, Justin K.; Volpp, Kevin G.; Paz-Soldan, Valerie; Behrman, Jere R.; Levy, Michael Z.
Abstract: Incentives are a useful tool in encouraging healthy behavior as part of public health initiatives. However, there remains concern about motivation crowd out—a decline in levels of motivation to undertake a behavior to below baseline levels after incentives have been removed—and few public health studies have assessed for motivation crowd out. Here, we assess the feasibility of identifying motivation crowd out following a lottery to promote participation in a Chagas disease vector control campaign. We look for evidence of crowd out in subsequent participation in the same behavior, a related behavior, and an unrelated behavior. We identified potential motivation crowd out for the same behavior, but not for related behavior or unrelated behaviors after lottery incentives are removed. Despite some limitations, we conclude that motivation crowd out is feasible to assess in large-scale trials of incentives.